DEVELOPMENT OF COMIC LEARNING MEDIA OF SOCIAL ARITHMETICS MATERIAL BY HIGHER ORDER THINKING SKILLS ORIENTED - Annisa Annisa; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research was motivated by the lack of comic learning media on social arithmetic material in schools. This study aims to develop comic learning media in HOTS oriented social arithmetic materials for junior high school / MTs students. This research is included in research and development using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were material experts, media experts, State Junior High School (SMP Negeri) 4 Sewon, and Muhammadiyah Junior High School (SMP Muhammadiyah) Sewon in Bantul regency. Data collection techniques used in this study are interviews used before product development. The research instrument used was interview guidelines to assess comic learning media that had been developed. Data analysis techniques use quantitative data analysis, converted into qualitative data with a Likert scale. Based on the results of the feasibility study of the product which was developed based on the calculation of the average score of the media expert obtained by 4.32 with very good criteria, from the expert material obtained at 4.29 with very good criteria, from the response of students in the small class test obtained at 4.38 with very good criteria, and from the students' responses to the trial of large class products obtained by 4.01 with good criteria. Based on these assessments, the mathematical comic learning media developed in social arithmetic is appropriate for the learning process.